PENGARUH KARAKTERISTIK IBU TERHADAP PEMBERIAN ASI EKSKLUSIF PADA BAYI USIA 0-6 BULAN DI BPM NURUL TRIANAWATI, SST SURABAYA - Uke Maharani Dewi (Jurnal Ilmiah Kesehatan, 2016)
Breastfeeding in Indonesia has become a culture, but the practice of breastfeeding is still far from the expected. The purpose of this study to determine the effect of maternal characteristics (age, education level, occupation, and number of children) on exclusive breastfeeding in infants aged 0 – 6 month in BPM. Nurul Trianawati, SST Surabaya. This research is descriptive research. Population in this study are all mothers with infants aged 0 – 6 month in BPM. Nurul Trianawati, SST Surabaya that as many as 20 respondents. Sampling using total sampling. Data collection was done by interview. Collected data is then processed and analyzed using statistical program (SPSS) version 16.0. Data analysis include univariate analyzes looking for frequency distribution, bivariate analysis with chi square test correlation Saphiro Wilk test. The result of the bivariate analysis showed significant effect between the mothers age, occupation, and number of children on exclusive breastfeeding in infants aged 0 – 6 month in BPM. Nurul Trianawati, SST Surabaya with significant value smaller than 5%.